2009
DOI: 10.1167/iovs.09-3619
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor-1 (PAI-1) Facilitates Retinal Angiogenesis in a Model of Oxygen-Induced Retinopathy

Abstract: Purpose Angiogenesis, or the formation of new retinal blood vessels is a key feature of many proliferative retinal diseases including diabetic retinopathy, retinal vein occlusions, and retinopathy of prematurity. The aim of the present study was to investigate the role of the serine proteinase inhibitor PAI-1 in facilitating retinal angiogenesis. Methods The temporal expression of PAI-1 was examined by real time PCR, western blotting and immunohistochemistry in retinal tissues from mice with oxygen-induced r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…PAI-1 is involved in cancer angiogenesis, metastasis and promotes angiogenesis by stimulating EC migration toward fibronectin [60]. It also plays a role during retinal angiogenesis [61] and has been demonstrated to support angiogenesis in cancer. Geis et al .…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 is involved in cancer angiogenesis, metastasis and promotes angiogenesis by stimulating EC migration toward fibronectin [60]. It also plays a role during retinal angiogenesis [61] and has been demonstrated to support angiogenesis in cancer. Geis et al .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Malme3M R cells may enhance the angiogenic potential of human endothelial cells via angiogenic factors such as VEGF and PAI-1. PAI-1 facilitates retinal angiogenesis (34) and is necessary for sonic hedgehog-induced cerebral angiogenesis (35). VEGF-B binds to VEGFRI and regulates PAI-1 activity (36).…”
Section: Mir-200bmentioning
confidence: 99%
“…4A), which confirmed that HA did not require VEGF to promote angiogenesis. PAI-1 protects endothelial cells from Fas-mediated apoptosis (Bajou et al, 2008), and facilitates retinal angiogenesis (Basu et al, 2009). These reports indicate the potential role of PAI-1 in angiogenesis.…”
Section: Ha Induces Expression Of Plasminogen Activator Inhibitor-1 (mentioning
confidence: 99%